EDUCATIONAL PROFESSIONALS AS SOCIO-LABOR TRAINING AGENTS FOR YOUTH WITH INTELLECTUAL FUNCTIONAL DIVERSITY - Negri Cortés, María Isabel (2017)
This paper seeks to describe and analyze the role of professionals in the field of education as one of the main agents who contribute to the socio-labor inclusion of youth with Intellectual Functional Diversity (IFD). Based on the complementarity of the quantitative and qualitative methods, we have delved into the significance of providing quality training to advisors and faculty, one which will enable them to foster the development of personal, social and labor skills and competencies in youth with IFD, so they can access employment and adulthood in an easier manner. Additionally, we have highlighted the significance of training these professionals in innovative methodologies to respond to their students’ diversity and promote the transferability of their learning to new contexts. To conclude, we have been aware of these professionals’ great commitment despite the lack of sufficient human and material resources.